2022
DOI: 10.3390/ijms23179859
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Laboratory Diagnosis of M-like Variants Related to Alpha1-Antitrypsin Deficiency

Abstract: Alpha1-antitrypsin (AAT) is a serine protease inhibitor that is encoded by the highly polymorphic SERPINA1 gene. Mutations in this gene can lead to AAT deficiency (AATD), which is associated with an increased risk of lung and/or liver disease. On the basis of electrophoretic migration, AAT variants are named with capital letters; M (medium) signifies the normal protein. Among pathological variants, the M-like ones represent a heterogeneous group of rare allelic variants that exhibit the same electrophoretic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Many rare variants are not easily diagnosed with routine laboratory techniques, thus contributing to misclassification and misdiagnosis. For example, phenotyping by IEF usually does not allow the precise identification of M-like AAT variants, such as M malton , M procida (40) as they are easily confused with M (normal) protein. Furthermore, Null (Q0) variants in heterozygosity are invisible to IEF and can only be indirectly observed through their effects on circulating levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many rare variants are not easily diagnosed with routine laboratory techniques, thus contributing to misclassification and misdiagnosis. For example, phenotyping by IEF usually does not allow the precise identification of M-like AAT variants, such as M malton , M procida (40) as they are easily confused with M (normal) protein. Furthermore, Null (Q0) variants in heterozygosity are invisible to IEF and can only be indirectly observed through their effects on circulating levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most rare alleles can only be detected by molecular biology techniques, such as SERPINA1 gene sequencing (1,41). Sometimes, depending on the complexity of the case, sequencing of exons might not be sufficiently informative and more extensive analysis by whole gene sequencing is required to detect rare exonic deletions, alterations in promoters or deep intronic regions not covered by standard sequencing (9,40). It has been recently demonstrated that the choice of diagnostic algorithm can have a significant impact on the accurate diagnosis of AATD, which is essential for appropriate medical care and treatment (42).…”
Section: Discussionmentioning
confidence: 99%